Riqueza e abundância de espécies em comunidades de abelhas Euglossina (Hymenoptera; Apidae) no corredor central da Mata Atlântica - Medeiros, Renata Lee dos Santos (2014)
The abiotic factors as the temperature, relative humidity, precipitation and altitude can exert influence in community Euglossine bees. The objectives of this study were 1 – To Identify the Euglossine bees species occurring in a restricted area from dense Ombrophilous Forest in the Environmental Protection Area of the Pratigi - Southern Bahia; 2 – To Characterize the monthly fluctuations in local abundance of these species, 3 – To Analyze if the abiotic factors (temperature, precipitation, humidity and altitude) affected the composition, richness and abundance of Euglossine bees throughout the year; 4 – To Check if there was a change in composition Euglossine bees species in an altitudinal gradient coastal to the continent. Euglossine males were collected one a month, for twelve months, from 9:00 am to 3:00 pm, with aromatic traps containing methyl cinnamate, vanillin, eucalyptol, benzyl acetate, methyl salicylate, eugenol and β-Ionone. A total of 1947 males distributed among 3 genera and 25 species were collected. The most abundant species were Euglossa carolina and Euglossa ignita. Two peaks of abundance were observed, the larger one in the dry season. There wasn’t significant influence of abiotic variables (temperature, humidity, precipitation and altitude) on species richness. The abundance was influenced by temperature and humidity. The Diversity (H’) and Dominance were influenced by altitude. The study reveal the importance of preserving Euglossine bees species in different phytophysiognomies within the same biome, once different phytophysiognomies can alter the pattern of richness and abundance of Euglossine bees species in the environment.